1989
DOI: 10.1016/s0010-9452(89)80044-9
|View full text |Cite
|
Sign up to set email alerts
|

Different Dimensions of Hand Preference That Relate to Skilled and Unskilled Activities

Abstract: Hand preference is multidimensional with two major factors and a variable number of minor factors. In the present factor analyses of hand preference, there was no evidence to support Healey, Liederman and Geschwind's (1986) suggestion that hand preference dimensions can be distinguished on the basis of those requiring movement of the distal musculature (fingers and hand) and those requiring movement of the proximal. The first factor reported here relates to "skilled" activities. Hand preference for the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
213
1
13

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(254 citation statements)
references
References 13 publications
23
213
1
13
Order By: Relevance
“…Specifically, the tube and ball tasks significantly correlated with each other, but neither of these measures correlated with the remaining four measures, which all significantly correlated with each other. These findings are similar to findings using factor analysis of human handedness measures (Annett, 1985;Healey, Liederman, & Geschwind, 1986;Porac & Coren, 1981;Steenhuis & Bryden, 1989) and are consistent with the hypothesis that handedness is not unidimensional and that different measures of hand preference may involve different motor or neural systems. For example, Healey et al (1986) had participants fill out a 52-item questionnaire in which they indicated their hand use on a 5-point Likert-type scale as 1 (right always), 2 (right preferred but sometimes use left), 3 (no preference), 4 (left preferred but sometimes use right), or 5 (left always).…”
supporting
confidence: 89%
“…Specifically, the tube and ball tasks significantly correlated with each other, but neither of these measures correlated with the remaining four measures, which all significantly correlated with each other. These findings are similar to findings using factor analysis of human handedness measures (Annett, 1985;Healey, Liederman, & Geschwind, 1986;Porac & Coren, 1981;Steenhuis & Bryden, 1989) and are consistent with the hypothesis that handedness is not unidimensional and that different measures of hand preference may involve different motor or neural systems. For example, Healey et al (1986) had participants fill out a 52-item questionnaire in which they indicated their hand use on a 5-point Likert-type scale as 1 (right always), 2 (right preferred but sometimes use left), 3 (no preference), 4 (left preferred but sometimes use right), or 5 (left always).…”
supporting
confidence: 89%
“…Several other studies have attempted to address this issue by investigating tasks of different complexity. Higher task complexity is expected to require a larger area of workspace covered by the dominant hand but some findings are inconsistent (Steenhuis & Bryden, 1989;Bryden, Pryde, & Roy, 1999). At present, the exact relationship between hand preference and hand dominance is unclear (see especially Guiard, 1988Guiard, , 1990.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the manual asymmetry observed in the population of left-handers is not simply a mirror reversal of the pattern shown by the righthanders (e.g., Peters, 1990). These distributional characteristics of the hypothesised handedness continuum might cause difficulties in interpreting correlations obtained with left-and right-handers together (see also Steenhuis, 1996).…”
Section: Hand Preference Analysesmentioning
confidence: 97%
“…Some of the participants were level 1 undergraduates and received course credit for their participation. Participants' handedness was assessed using a 15-item abbreviated version of the Waterloo Handedness Questionnaire (WHQ; Steenhuis & Bryden, 1989, scores can range from -30 to +30). Sighting dominance was assessed using a variant the Miles A-B-C test (Miles, 1929), which requires aligning a distant target with a slot produced by two hand held cards at arms' length.…”
Section: Participantsmentioning
confidence: 99%